2010
DOI: 10.1128/jcm.00228-10
|View full text |Cite
|
Sign up to set email alerts
|

Diarrheagenic Escherichia coli Markers and Phenotypes among Fecal E. coli Isolates Collected from Nicaraguan Infants

Abstract: We analyzed the prevalence of diarrheagenic Escherichia coli (DEC) markers and common phenotypes in 2,164 E. coli isolates from 282 DEC-positive samples. Enteropathogenic E. coli (EPEC) and enteroaggregative E. coli (EAEC) were very diverse and were not correlated with diarrhea. Enterotoxigenic E. coli (ETEC) estA and enterohemorrhagic E. coli (EHEC) belonged to a few phenotypes and were significantly correlated with diarrhea.In Nicaragua, diarrheagenic Escherichia coli (DEC) strains are considered to be commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
2
2
0
Order By: Relevance
“…So, the data demonstrated in this study is in disagreement with previous findings from such countries. On the other hand, results from Nicaragua, Peru, and Brazilian cities have found almost the same scenario herein described, that is, lower frequencies for STEC when compared with other DEC pathotypes .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…So, the data demonstrated in this study is in disagreement with previous findings from such countries. On the other hand, results from Nicaragua, Peru, and Brazilian cities have found almost the same scenario herein described, that is, lower frequencies for STEC when compared with other DEC pathotypes .…”
Section: Resultssupporting
confidence: 82%
“…So, the data demonstrated in this study is in disagreement with previous findings from such countries. On the other hand, results from Nicaragua, Peru, and Brazilian cities have found almost the same scenario herein described, that is, lower frequencies for STEC when compared with other DEC pathotypes (31,(38)(39)(40)(41). Curiously, EAEC and aEPEC were detected in similar frequencies between both the diarrheic and control children studied (Table 3), thus making it difficult to associate these DEC pathotypes with diarrheal disease, even when statistical analyses were performed considering the different age groups of this study (data not shown).…”
Section: Resultssupporting
confidence: 79%
“…EPEC was detected significantly more frequently in non-diarrheal children (25.0z) than in diarrheal children (0.8z) (P º 0.0001). Previous studies reported that the rate of atypical EPEC isolation from children with diarrhea was not significantly different from the rate of isolation from children without diarrhea (4)(5)(6)(7). One of the explanations may be that most of the diarrheal children were already prescribed antibiotics before hospitalization.…”
mentioning
confidence: 85%
“…DEC can be classified into five major categories on the basis of their specific virulence properties: Shiga toxin-producing E. coli (STEC), enteropathogenic E. coli (EPEC), enteroaggregative E. coli (EAEC), enterotoxigenic E. coli (ETEC), and enteroinvasive E. coli (EIEC) (2). The importance of DEC has been reported in developing countries (3)(4)(5)(6)(7). In Indonesia, while a high incidence of diarrhea in children has been reported (8,9), no study has compared diarrheal children with non-diarrrheal or healthy children to elucidate the role of DEC in pediatric diarrheal diseases.…”
mentioning
confidence: 99%